Leadership Communication - BARRETT, Deborah J (McGraw - Hill Book Company, 2002)
Leadership Communication is a text to guide current and potential leaders in developing the communication capabilities needed to be transformational leaders. It brings together managerial communication and concepts of emotional intelligence to create a new model of communication skills and strategies for corporate leaders. The Third Edition of Leadership Communication has been updated and changed specifically to emphasize transformational leadership, ethics, and integrity and to include guidance on the use of current social media.